2019
DOI: 10.21272/sec.3(2).15-30.2019
|View full text |Cite
|
Sign up to set email alerts
|

Decoupling CO2 Emissions in Nordic countries: Panel Data Analysis

Abstract: The paper summarizes the principal notions of Kuznets hypothesis and Environmental Kuznets Curve as well as their implications in Nordic countries as examined by eminent scholars.The survey of huge literatures on this issue indicated that the absolute and relative decoupling of CO2 emissions were quite relevant for those countries who have been playing leading role in combating emissions to fulfill Paris Agreement. The main purpose of the research is to test empirically the decoupling CO2 emissions per capita … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…Meanwhile, Chovancová and Tej (2020) found empirical evidence of decoupling the economic growth of the energy sector and greenhouse emissions produced by the energy sector in 1995-2016 in V4 countries. While Bhowmik (2019) proved that there was is an inverse U-shape relationship between CO2 emission per capita and GDP per capita in the Nordic countries during 1970-2016. Therefore, it proves the hypothesis that in current conditions, the country's environmental policy might be focused mostly on strengthening energy security and less on limitation of greenhouse gas emission.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Meanwhile, Chovancová and Tej (2020) found empirical evidence of decoupling the economic growth of the energy sector and greenhouse emissions produced by the energy sector in 1995-2016 in V4 countries. While Bhowmik (2019) proved that there was is an inverse U-shape relationship between CO2 emission per capita and GDP per capita in the Nordic countries during 1970-2016. Therefore, it proves the hypothesis that in current conditions, the country's environmental policy might be focused mostly on strengthening energy security and less on limitation of greenhouse gas emission.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some researchers have devoted their work to the study of energy independence of all types of resources and investments in renewable energy as a guarantee of sustainable development [9][10][11][12][13][14][15][16][17]. The study of forecasting of the country's development strategy based on social progress and macroeconomic stability, lifelong learning, as well as the country's food security and the role of sustainable development have been reflected in numerous scientific papers [18][19][20][21][22][23][24][25][26].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results of the generalisation of scientific research showed that researchers analysed a different set of factors influencing the transformation processes of the transition to a climate-free economy. Thus, scientists have identified social (Palienko et al, 2017;, ecological Mačaitytė et al, 2018); Matsenko et al, 2017), economic (Bhowmik, 2019;Bilan et al, 2019) determinants of the impact on macroeconomic stability in reforming the energy sector in the direction of carbon neutrality.…”
Section: Literature Reviewmentioning
confidence: 99%